Pemanfaatan Smartphone dalam Pembelajaran IPAS di Kelas IV SD Negeri 3 Jenengan Kecamatan Sawit Kabupaten Boyolali - Nunung Wulandari; Muhammad Hafid Al Husain; Syamsul Huda Rohmadi (JoEMS (Journal of Education and Management Studies), 2026)
Purpose: This study aims to describe the use of smartphones in the teaching of Natural and Social Sciences (IPAS) in Year 4 at SD Negeri 3 Jenengan, Sawit Sub-district, Boyolali Regency. Methodology/approach: A qualitative, descriptive approach was employed. The research subject was the Year 4 teacher, whilst the object of study was the use of smartphones as a teaching aid for IPAS. Data collection techniques included observation, in-depth interviews and documentation, which were subsequently analysed using the Miles and Huberman interactive model. Findings: The use of smartphones was supported by four main factors, namely the availability of school infrastructure, an adequate internet connection, a variety of learning applications (such as Quizizz, Google Earth and YouTube), and active support from pupils’ parents. Teachers implemented the use of smartphones through three structured stages: planning (by adapting applications to learning outcomes), implementation (with intensive guidance), and evaluation (through digital quizzes and feedback via a WhatsApp group). A key finding of this study is that the success of smartphone integration is largely determined by the readiness of the supporting ecosystem beyond the teacher, particularly the role of parents in providing access to devices and internet data allowances, as well as the teacher’s ability to mitigate the risk of inappropriate device use during the learning process. Practical implications: The use of smartphones makes it easier for pupils to access a wide range of information via the internet, enabling them to learn independently. Furthermore, teachers can easily share teaching materials, set assignments and provide feedback via instant messaging platforms or learning applications. Originality/novelty: This study offers a novel focus on the use of smartphones in IPAS learning in Year 4 of primary school, covering the stages of planning, implementation and evaluation. In addition to examining the positive impacts on learning outcomes, this study also reveals the negative impacts in a more comprehensive manner and highlights the role of parental support and the use of digital applications in learning.